2403. Comparison of Daptomycin Combination Therapy With Ceftaroline or Oxacillin Against Methicillin-Resistant Staphylococcus aureus (MRSA) Isolates Causing Persistent Bacteremia. (26th November 2018) - Bouchard, Jeannette; Jones, Chelsea; Kline, Ellen; Oleksiuk, Louise-Marie; Shields, Ryan K
Abstract: Background: Increasing evidence suggests that daptomycin (DAP) demonstrates in vitro synergy in combination with other anti-staphylococcal agents, including ceftaroline (CPT) and oxacillin (OXA), against MRSA. Nevertheless, optimal combinations remain undefined. Here, our objective was to compare DAP in combination with CPT or OXA against MRSA bloodstream isolates collected from patients with persistent bacteremia despite >7 days of vancomycin treatment. Methods: Minimum inhibitory concentrations (MICs) for DAP, CPT, and OXA were determined in duplicate by reference broth microdilution methods. We used time-kill analyses (TKA) to test free peak concentrations (fCmax ) of DAP (8 µg/mL), CPT (16 µg/mL), and OXA (4 µg/mL) alone and in combination against 1 × 10 8 CFU/mL to simulate high-inocula infections. Bactericidal and synergistic activity were defined as a ≥3-log10 decrease in CFU/mL and >2-log10 decrease in CFU/mL in combination compared with the most active single agent, respectively, at 24 hours. Results: A representative isolate was selected from 12 patients with persistent MRSA bacteremia. Median (range) MICs were 0.5 (0.5–1), 0.5 (0.5–1), and 64 (64–≥128) µg/mL for DAP, CPT, and OXA, respectively. By TKA ( n = 5 isolates), median log-kills were −3.81, −1.90, and +1.99 log10 CFU/mL for DAP, CPT, OXA, respectively. Corresponding rates of bactericidal activity were 80%, 20%, and 0%, respectively. In combination, median log-kills were −7.83 and −4.82 log10 CFU/mL for DAP+CPT and DAP+OXA, respectively ( P = 0.111; Figure 1). DAP was synergistic in combination with CPT or OXA against 80% and 60% of isolates, respectively. Median log-kills in combination with CPT or OXA were higher than DAP alone ( P = 0.003 and P = 0.0497, respectively). At 24 hours, colony counts were below the lower limit of detection (50 CFU/mL) against 60% and 20% of isolates exposed to DAP+CPT or DAP+OXA, respectively. Conclusion: Among persistent MRSA bloodstream isolates, combinations of DAP + CPT or OXA demonstrates synergy and statistically greater killing effects in vitro at fCmax concentrations than DAP alone. Log-kills were greatest with DAP+CPT, which merits further validation in pre-clinical models. Disclosures: All authors: No reported disclosures.